Background thermal depolarization of electrons in storage rings - Guimarães, A. C C [UNESP]; Matsas, G. E A [UNESP]; Vanzella, D. A T [UNESP] (American Physical Society (APS), 1998)
We discuss the influence of the background thermal bath on the depolarization of electrons in high-energy storage rings, and on the photon emission associated with the spin flip. We focus, in particular, on electrons at CERN LEP. We show that in a certain interval of solid angles the photon emission is enhanced several orders of magnitude because of the presence of the thermal bath. Notwithstanding, the overall depolarization induced by the background thermal bath at LEP conditions is much smaller than the one induced by plain acceleration at zero temperature and can be neglected in practical situations. Eventually we discuss under what conditions the background thermal bath can enhance the overall depolarization by several orders of magnitude.